THE PULMONARY ARTERIAL HYPERTENSION ASSOCIATED WITH VENTRICULAR SEPTAL DEFECTS: A SINGLE-CENTRE EXPERIENCE IN THE REPUBLIC OF KAZAKHSTAN - Mullen, Aigerim; Abzaliyev, Kuat; Butrous, Ghazwan (Interdisciplinary Approaches to Medicine, 2020)
The aim of this study was to evaluate the impact of pulmonary arterial hypertension on outcomes following surgical or transcatheter repair of isolated ventricular septal defect in the Republic of Kazakhstan. Echocardiography and catheterisation reports of children with isolated ventricular septal defect complicated pulmonary arterial hypertension surgical or transcatheter repair between 2012 and 2016.Amongst 38 children ventricular septal defect mean size was 10.92 ± 6.38mm. The mean systolic pressure in the right ventricle on Echocardiography was 55.42 ± 18.47 mmHg. Mean pulmonary arterial pressure by right heart catheterisation was 52.12 ± 29.44 mmHg. The mean end diastolic index for all children was registered as 76.78±19.58ml. Cardiac output was preserved in all children. In the pre-operative period, 9 of these children were treated with sildenafil.One week after the operation, mean right ventricle systolic pressure decreased as for children who did not receive preoperative sildenafil (from 55.5±14.8mmHg to 32.2±14.4mmHg) (p <0.01), as for children who did (from 81.4±10.3mmHg. to 48.1±12.4mmHg (p value < 0.01)). End diastolic index normalized in 92.5% of cases. Right ventricle systolic pressure decreased >40% in all children a month after the surgery.In our study prescription of specific drug therapy of pulmonary arterial hypertension with the purpose of preparing for surgery has no effect on the effectiveness of surgical treatment of ventricular septal defect. We had had no early postoperative mortality.